HIRARKI PENCEGAHAN FRAUD (KONSEP PENGAWASAN BANK INDONESIA) PADA AKAD KEUANGAN DI BANK SYARIAH - Wilchan Robain; Abdul Rahman (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2022)
The purpose of this study was to find a ranking hierarchy for fraud prevention (the concept of Bank Indonesia supervision) in accordance with SE Bank Indonesia No. 13/28/DPNP Year 2011 on financial contracts at Islamic banks. This study uses a combination of quantitative and qualitative methods, analyzes data using Analytical Networking Processes (ANP) through Super Decision Software, conducts open and in-depth interviews with 9 respondents, Focus Group Discussion (FGD) with practitioners and experts in Islamic finance. In this case, a hierarchy of fraud prevention rating structures was found (in financial contracts at Islamic banks, 33.1% active management monitoring, 27.6% internal and external environmental conditions, 23% monitoring, evaluation and follow-up, 22.3 organizations and answers %, business complexity 20.1%, then the next rank is investigation, reporting and sanctions, detection, control and monitoring, prevention, potential, types and risks of fraud, the resources required range from 15.6% to 10.6%.